ANALISIS PASIR SUNGAI PANGIAN SEBAGAI BAHAN AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Arron O. T. Woruntu; Nicky W. Rampengan; Metsi Daud, (Sustainable Construction (SUSCON), 2024)
Concrete is a widely utilized construction material in contemporary building structures. It is formed by combining portland cement, water, sand, and gravel. The strength of concrete is inversely proportional to the FAS value, meaning that higher FAS values indicate lower concrete quality. The motivation behind this research stems from the limited information available regarding Pangian river sand. The objective of this study is to assess the characteristics of Pangian river sand and determine the compressive strength of high-quality concrete. The concrete specimens used in this investigation were cylindrical in shape, with a diameter of 15 cm and a height of 30 cm, resulting in a total of 6 test objects. The average slump height achieved for concrete with a quality of 24 Mpa and FAS of 0.50 was 86.6 mm, while for concrete with a quality of 29 Mpa and FAS of 0.45, the average slump height was 88 mm. Furthermore, the average compressive strength of the concrete samples was determined. For concrete with a quality of 24 Mpa and FAS of 0.50, the average compressive strength was 25.6 Mpa, representing a 6.6% increase from the planned quality. Similarly, for concrete with a quality of 29 Mpa and FAS of 0.45, the average compressive strength was 31.4 Mpa, indicating an 8.275% increase from the planned quality. Consequently, it can be inferred that Pangian river sand can be effectively employed as a fine aggregate material in concrete mixtures.